Marine Biota-Derived Hydroxyapatite as a Bone Graft Material: A Scoping Review of Hydroxyapatite from Shell-Based Sources - Rahadian, Arief; Hutami, Islamy Rahma (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Backgrounds: Restoring damaged or diseased bone is a major challenge in dentistry. Marine biota, such as seashells, crustacean shells, and fish bones, are rich in calcium and can be processed into safe, biodegradable materials that support bone healing. These natural sources are gaining attention for use as bone graft substitutes because they are biocompatible, widely available, and promote bone growth. Purpose: This review aims to discuss and analyze the potential of marine biota as bone graft materials rich in calcium hydroxyapatite for use in bone regeneration, with a particular focus on their clinical relevance in dentistry. Methods: A scoping review was conducted using Google Scholar, PubMed, and ScienceDirect databases to identify relevant studies published between 2015 and 2025. Results: An initial total of 134.007 articles were identified across the three databases. After removing duplicates and screening based on title and abstract relevance to the inclusion criteria, 2.836 articles remained. A further selection process narrowed these down to 452 full-text articles, of which 433 were excluded due to incompatibility with the review focus. Finally, 19 studies were included in this review and analyzed for their methodology, findings, and clinical implications. Discussion: Many studies have shown that marine biota can be used as effective bone graft materials. Their high calcium content, porous structure, and compatibility with body tissues help support cell attachment, growth, and new bone formation. These materials can be used in dental procedures to help regenerate bone and repair defects. Conclusion: Marine-derived materials, especially from mollusks and crustaceans, are similar to human bone and show great potential as alternatives to synthetic bone grafts. Their natural properties and ability to support bone healing make them a promising, sustainable option for dental and oral bone repair.